The Practice of Money Politics in Village Head Elections and Its Effect on The Participation Level of Beginner Voters - Hasan, Effendi; Aminah, Aminah; Haji Hamil, Haji Jamaie; Mukhrijal, Mukhrijal (Journal of Governance and Public Policy, 2023)
General election is a form of democratic system implementation. This democratic system is carried out to the lowest level in the government system, namely in the general election of village heads. However, in practice, the village head election process is still not optimal due to various forms of fraud. One of which is the practice of money politics. Money politics aims to influence the voters' votes so that they are influenced to choose a candidate who provides them with assistance in the form of money or goods and services. The case of money politics is getting stronger in the run-up to the election, and the targets of money politics are not only voters who have held elections before but also beginner voters. This study aimed to determine the practice of money politics in the election of village heads and its effect on the level of participation of novice voters. The research method used is descriptive quantitative. Data were collected through questionnaires and interviews. The research used data interpretation assisted with statistical applications, SPSS, to analyze the data. The results showed that the money politics practices that occurred in the election of the Village Head in Gampong Gunong Meulinteung were in the form of money that is 64 people (76%), goods that is 46 people (57%), and services that is 47 people (58%). The correlation test results show a value of 0.276, where the influence of money politics on novice voters in the Gampong Gunong Meulinteung Village Head Election in 2019 is 7.6%. It means that it has little effect on novice voters. The rest, amounting to 92.4% of novice voters, chose the Village Head candidate based on other factors such as age, education, and the candidate’s personality. Therefore, all forms of money politics should be eliminated in the general election so that the implementation of democracy in Indonesia can run well. In addition, it is also necessary to provide political education for novice voters, and it is hoped that the village government will form a task force that acts to eradicate cases of election fraud.